Pembuatan Game Edukasi Bahasa Inggris Untuk Anak Kelas 1-2 SD Menggunakan Flash - Lukito, Hadi Wijaya; Purba, Kristo Radion; Palit, Henry Novianus (Jurnal Infra, 2015)
Elementary school children generally like to play games, as a survey reported that more than a quarter of children around the world have their handheld computers before they reach eight years of age. Children may reason that games can be used as a mean of refreshing when they get bored in study. However, in reality many children play games not useful to improve their knowledge and even become addicted and forget to study.In this manuscript, author make an English educational game targeted for elementary 1-2 school children. Children are expected to enjoy the game while learning English.This application has been reviewed by some elementary school English teachers. They responded that the gameâs content matches well with the teaching material taught in their class.